Acute Total Knee Replacement in Rheumatoid Arthritis Patients with Proximal Tibial Fractures: A Case Series - Mirzatolooei, Fardin; Tabrizi, Ali; Safari, Mir Bahram; Shishavan, Seyed Amir Mahlisha Kazemi (The Journal of Knee Surgery, 2020)
Management of proximal tibial fractures is a challenging issue in patients with rheumatoid arthritis (RA). In the present study, we aimed to describe our experience of acute total knee replacement in RA patients. This case series included 11 RA patients with simultaneous insufficiency fractures of the proximal tibia, who were treated by acute total knee replacement. Midterm functional results, severity of pain, Hospital for Special Surgery (HSS), and Knee Society Score (KSS) parameters were evaluated in this study. The patients were followed up for 24 months. Eleven women with proximal tibial fractures and history of RA (mean age: 54.3 ± 4.7 years) were enrolled in this study. The mean score of Tegner activity scale was 2.2 ± 1.4 preoperatively, which significantly improved to 4.3 ± 1.4 postoperatively (p < 0.001). The two sections of KSS (knee and function section) averaged 88.7 ± 5.4 and 59.4 ± 8.2, respectively. There wasn't poor outcome and excellent result was in knee section 54.5% and function section 36.3% based on KSS. The mean score of pain severity during normal activity before fracture was 65.2 ± 12.3, which significantly reduced to 35.5 ± 11.3 in the final follow-up (p = 0.02). The score of HSS scale improved from 42 (range: 16–58) in the preoperative stage to 78 (range: 72–91) after surgery (p < 0.001). In the 6-month follow-up, deep vein thrombosis was reported in two patients. The time required to return to normal activity was 5.5 ± 2.3 months. Based on the findings, total knee replacement therapy in patients with RA and proximal tibial fractures produced excellent clinical outcomes, which led to rapid return to normal activity. This is a Level IV, therapeutic study.
Keywords: rheumatoid arthritis; osteoporosis; proximal tibial fractures; total knee replacement